RETRACTED: Suppression of epileptogenesis-associated changes in response to seizures in FGF22-deficient mice - Lee, Clara H.; Umemori, Hisashi (Frontiers in Cellular Neuroscience, 2013)
In the developing hippocampus, fibroblast growth factor (FGF) 22 promotes the formation of excitatory presynaptic terminals. Remarkably, FGF22 knockout (KO) mice show resistance to generalized seizures in adults as assessed by chemical kindling, a model that is widely used to study epileptogenesis (Terauchi et al., 2010). Repeated injections of low dose pentylenetetrazol (PTZ) induce generalized seizures ("kindled") in wild type (WT) mice. With additional PTZ injections, FGF22KO mice do show moderate seizures, but they do not kindle. Thus, analyses of how FGF22 impacts seizure susceptibility will contribute to the better understanding of the molecular and cellular mechanisms of epileptogenesis. To decipher the roles of FGF22 in the seizure phenotype, we examine four pathophysiological changes in the hippocampus associated with epileptogenesis: enhancement of dentate neurogenesis, hilar ectopic dentate granule cells (DGCs), increase in hilar cell death, and formation of mossy fiber sprouting (MFS). Dentate neurogenesis is enhanced, hilar ectopic DGCs appeared, and hilar cell death is increased in PTZ-kindled WT mice relative to PBS-injected WT mice. Even in WT mice with fewer PTZ injections, which showed only mild seizures (so were not kindled), neurogenesis, hilar ectopic DGCs, and hilar cell death are increased, suggesting that mild seizures are enough to induce these changes in WT mice. In contrast, PTZ-injected FGF22KO mice do not show these changes despite having moderate seizures: neurogenesis is rather suppressed, hilar ectopic DGCs do not appear, and hilar cell death is unchanged in PTZ-injected FGF22KO mice relative to PBS-injected FGF22KO mice. These results indicate that FGF22 plays important roles in controlling neurogenesis, ectopic migration of DGCs, and hilar cell death after seizures, which may contribute to the generalized seizure-resistant phenotype of FGF22KO mice and suggests a possibility that inhibition of FGF22 may alleviate epileptogenesis.